Just breathe : mastering breathwork for success in life, love, business, and beyond - Brulé, Dan (Atria/Enliven Books, 2017)
"Reduce stress and anxiety, increase your productivity, detox your body, balance your health, and find the path to greater mindfulness with this collection of signature breathing techniques by the world's leading breathmaster, Dan Brule. What if you could control your outcomes and change results simply by controlling your breath? Now you can. In this definitive handbook, world-renown pioneer of breathwork Dan Brule shares for the first-time his Breath Mastery technique that has helped more than 100,000 people in over forty-five countries. Just Breathe is a simple and revolutionary guide that reveals the secret behind what the elite athletes, champion martial artists, Navy SEAL warriors, and spiritual yogis have always known--when you control your breathing you can control your state of well-being and level of performance. So if you want to optimize your health, clear and calm your mind, and spark peak performance--the secret to unlock and sustain these results comes from a free and natural resource that's right under your nose. From high stress, critical situations to everyday challenges, Just Breathe will show you how to harness your awareness and conscious breathing to benefit your body, mind, and spirit. Breathwork benefits a wide range of issues including: managing acute/chronic pain; help with insomnia, weight loss, attention deficit, anxiety, depression, PTSD, and grief; improves intuition, creativity, mindfulness, self-esteem, leadership, and much more. Just Breathe will show you the skills andtools to breathe your way to optimum health, ultimate potential, and peak performance"--